Melioidosis case series. (September 2019) - Merrick, B.; Jones, T.; Ong, E.; Price, D.A.; Schwab, U.
Abstract: Melioidosis is a potentially fatal infection caused by Burkholderia pseudomallei, a bacterium endemic to certain tropical and subtropical world regions. It most frequently enters the body through small abrasions on the feet or lower limbs when individuals walk barefoot, or in open footwear, through contaminated wet or muddy environments. We report on three female cases successfully treated for melioidosis within the Newcastle upon Tyne NHS Hospitals over a 12-month period; a 52-year-old with a mediastinal abscess, a 38-year-old with an intra-cerebral abscess, and a 69-year-old with pneumonia and bacteraemia. Two patients were diabetic, the latter with established microvascular complications, but the third patient had no immunosuppressive risk factor identified. All had recently travelled to Thailand, although one remained solely within the confines of her holiday resort and another did not leave the city of Pattaya. Clinicians must remain vigilant to the potential for imported cases of melioidosis into the UK in travellers returning from endemic areas, such as Southeast Asia. Highlights: Melioidosis is a rare but important cause of sepsis in returning travellers from endemic world regions such as Southeast Asia Clinical presentations may include, but are not limited to, pneumonia, bacteraemia and abscesses Disease is seen more frequently, and more severe, in diabetics, alcoholics, and patients with chronic kidney disease B. pseudomallei is resistant to many 1st line antimicrobials - initial treatment with meropenem or ceftazidime is recommended Prolonged (3 months) consolidation therapy with co-trimoxazole reduces the rates of disease relapse